The MODEL OF THE VISITOR GAME FOR TEACHING AND LEARNING READING EXPLANATION TEXT FOR ELEVENTH GRADE STUDENTS: MODEL VISITOR GAME UNTUK MENGAJAR DAN MEMPELAJARI MEMBACA TEKS PENJELASAN SISWA KELAS XI - Wiwin Dwi Santika; Supriyono; Bahrul Ulum (Prodi Tadris Bahasa Inggris, 2023)
This research is research and development (R and D). The subject of this research was 30 students of from SMAN 1 Sutojayan, SMAN 1 Kademangan, and SMAN 4 Blitar also six teachers for a random school in Blitar Regency. This study used a quantitative approach using a questionnaire and qualitative by using interviews, observations, and document. The result of the research showed that; (1) the model of The Visitor game to teaching and learning reading for the eleventh grade students’ in high school students especially learning explanation text with 2 guide books that are guide book for teacher, and guide book for students. (2) The developed “The Visitor Game” game was valid, it proved by the result of the content English material validation (89%) and media validation (82,2%) (3) Students’ and teachers' gave positive responses toward the develop “The Visitor” game as a learning media reflected from the resulting questionnaire given 83,4% from students and 85% from teachers. From the result above, it can be concluded that the developed “The Visitor” game was very valid and appropriate to be applied as an alternative media for teaching and learning reading especially explanation text on the eleventh grade students’ in senior high school